Effect of fixed orthodontic appliances on self-assessment and diagnosis of halitosis in undergraduate dental students - Diego Dantas Lopes dos Santos; João Felipe Besegato; Sâmmea Martins Vieira; Andrea Abi Rached Dantas; Aryvelto Miranda Silva; Alexandre Monteiro da Silva (Wolters Kluwer Medknow Publications, 2021)
Background: The effects of fixed orthodontic therapy on the occurrence of halitosis are not yet fully understood. This study aimed to evaluate the effect of fixed orthodontic appliances on self-assessment and diagnosis of halitosis in undergraduate dental students. Materials and Methods: Sixty-two undergraduate dental students were included in this cross-sectional study. Two groups (n = 31 per group) were composed of participants with (study group) or without (control group) fixed orthodontic appliance. Halitosis self-assessment and clinical diagnosis were assessed using a visual analogic scale (VAS) and sulfur volatile compounds (SVCs) assessment, respectively. The subjective (VAS) and objective (SVC) malodor assessments were classified in absence, light, moderate, or severe malodor. Chi-square Pearson test and Spearman's correlation were applied for data analysis, with a significance level of 5%. Results: The use of fixed orthodontic appliances had no effect on self-assessment (P = 0.490) or clinical diagnosis (P = 0.610) of halitosis. Self-assessment was not significantly associated with the diagnosis of halitosis regardless the use of fixed orthodontic appliance (P ≥ 0.737). Male participants showed higher diagnosis of halitosis (P = 0.007). SVC measurements showed the absence of halitosis in 51.6% and 58.1% of participants with or without orthodontic appliances, respectively. Conclusion: The use of fixed orthodontic appliances affected the self-assessment of halitosis but no SVC measurements. It was not verified a correlation between subjective and objective methods to diagnose halitosis in dental students.